2003
DOI: 10.1046/j.1365-2648.2003.02756.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical care nursing research priorities in Hong Kong

Abstract: With the re-structuring of Hong Kong's health care system, critical care nurses are expected to take an active role in advancing the profession, and to be accountable for improving patient outcomes by use of effective, evidence-based interventions. The research priorities identified in this study may provide impetus and direction for critical care nursing research initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Organizational and professional issues were also identified as priority research areas. These priorities are not dissimilar to many of the research priorities previously identified in intensive care nursing (1,2,(16)(17)(18)(19). Studies on research priorities in intensive care have been conducted by several critical care nursing organizations around the world.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Organizational and professional issues were also identified as priority research areas. These priorities are not dissimilar to many of the research priorities previously identified in intensive care nursing (1,2,(16)(17)(18)(19). Studies on research priorities in intensive care have been conducted by several critical care nursing organizations around the world.…”
Section: Discussionmentioning
confidence: 70%
“…They found that the top priorities included patient issues related to neurological care, pain/sedation/comfort, best practice at the end of life, and ventilation strategies, as well as two priorities related to professional issues about nurses' stress/burnout and professional development needs. In a Delphi study undertaken with nurses from the Hong Kong Critical Care Nursing Association in 2003, priorities were mostly related to patient and family issues such as the use of therapeutic touch to relieve pain and anxiety, reducing fatigue in weaning, reducing family stress, and family participation in patient care (17). The top research priorities as identified in our study are related to end-of-life practices, pain management, nursing education and competencies, reducing healthcare-associated infections, staffing levels, and improving evidence-based nursing practice.…”
Section: Discussionmentioning
confidence: 99%
“…As geriatric oncology is considered to be a specialised area, selection of this expert panel was well considered, and includes contributions from a wide range of experts. Overall, during the consultation process, attrition rates were low, ensuring the validity of the final results (Hasson et al, 2000, Lopez, 2003). …”
Section: Discussionmentioning
confidence: 99%
“…From the 33 experts invited and having accepted to participate, 26 completed the first round, 25 completed the second round and 23 the third and final round (Table 1). Attrition rate in round 1 was 21.2%, in round 2 3.8% and in round 3 8%, corresponding to a response rate of 78.8%, 96.2% and 92% in each round, respectively, which is above the recommended rate of 70% in order to maintain rigor [44,45] and adequate to guarantee the validity of the results [46]. Statistical analysis revealed that internal consistency was reached simultaneously for the five of the six sets of items on the third round (Table 3).…”
Section: Resultsmentioning
confidence: 91%